REVIEW JURNAL : PENGARUH BERBAGAI JENIS BAHAN PENGIKAT TERHADAP SIFAT FISIK DAN MEKANIK TABLET PARASETAMOL - Febriyanti Helia Putri; Indira Manilet; Siti Jariah; Yulistia Budianti Soemarie (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2026)
Paracetamol is an analgesic–antipyretic drug commonly formulated as a tablet dosage form. Binders play an important role in determining the physical and mechanical quality of tablets. This journal review aims to evaluate the effect of various types of binders on the physical and mechanical properties of paracetamol tablets based on studies published within the last decade. The results indicate that the type and concentration of binders influence tablet hardness, friability, and disintegration time. Excessive binder concentration may adversely affect tablet performance by increasing tablet hardness and prolonging disintegration time, while natural binders show potential as alternative binding agents in paracetamol tablet formulations.